Influence of loading conditions on the shear capacity of post-tensioned beams with low shear reinforcement ratios. (1st September 2018) - Huber, Patrick; Huber, Tobias; Kollegger, Johann
Highlights: The shear behaviour of post-tensioned beams under different loading conditions was investigated experimentally. Digital image correlation (DIC) was used to track the development and kinematics of critical flexural-shear cracks. The experimental measurements allowed the quantification of various shear transfer actions. Arching action contributes significantly to the shear resistance of prestressed beams. Abstract: The majority of shear tests reported in the literature has been performed on simply supported reinforced concrete beams under point loads. In contrast, this paper focuses on the shear behaviour of post-tensioned T-beams with no or a minimum amount of transverse reinforcement under various loading conditions. Several test setups were used to investigate the influence of different distributions of the internal forces (due to uniformly distributed load and point loads, respectively) and of the shear slenderness on the shear resistance of the beams. Furthermore, the difference in the shear responses at the end support and the intermediate support of the beams was analysed using the experimental results. The experimental programme consisted of eight shear tests carried out on four specimens. With the aid of close-range photogrammetry, detailed measurements of the kinematics of the critical flexural shear cracks were taken. Linking well-known constitutive laws for concrete and steel with the relationship between the opening and sliding of critical cracks (determined using digital image correlation of experimental results) allowed the contributions of several shear transfer actions to the shear resistance to be estimated. In this paper, it is demonstrated that this approach leads to a better mechanical understanding of the actual shear behaviour of post-tensioned beams. The analysis illustrates that arching action plays a major role regarding the shear resistance of slender post-tensioned beams.